A STUDY ON PIGEONS(Columba livia) CESTODES INFECTION IN DIYALA PROVINCE - Al-Bayati, Nagham Yassin (Diyala Agricultural Sciences Journal, 2011)
The study was conducted to identify different cestodes infecting pigeons from various regions in Diyala province. The total prevalence were 73.01%. Three genera of cestodes were diagnosed and identified (Aporina delafondi , Cotugnia intermedia and Raillientina microcantha ). Parasitological findings of feces and guts examined for all type of cestodes in birds revealed three degree of inflections depending on the number of worms/bird. The results showed that the infected birds had significant decrease in P.C.V. (20.93%), Total number of R.B.C. (2.28 c*10/mm) and HB concentration (5.88 gm/100ml) in birds especially in severe (heavily) infections with cestodes. Results also show increase in total white blood cells (leucocytosis) specifically eosinophils (22.03 c*10/mm) in infected pigeons. The results showed bad biometric status and bad nutrient as compared with control group.